GEOLOGICAL-PETROGRAPHYCAL CHARACTERISTIC AND THE MAIN GENESIS FEATURES OF THE SECONDARY QUARTZITES OF PKHRUT-LERNADZOR'S ORE DEPOSITE: (Syunik Marz, Armenia) (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
On the base of field geological-petrographycal and microscopic investigations in the Pkhrut-Lernadzor ore field the uranium bearing widespread formation of the secondary quartzite have been carried out.
Keywords: Pkhrut-Lernadzor ore field; secondary quartzite; uranium bearing